Improving Students’ Learning Outcomes Using the Simulation Method in Islamic Religious Education (PAI) Subjects for Grade V at SD IT Baitul Qur’an Panti - Mayenni Fitri (BiCED Proceeding, 2024)
This study aims to improve the learning outcomes of fifth-grade students at SD IT Baitul Qur'an Panti by applying the Simulation method in teaching the topic of Infak. The research was conducted in two cycles: cycle I and cycle II. The findings indicate that in cycle I, although there was an improvement in student learning outcomes, some students did not achieve the Minimum Mastery Criteria (KKM). However, in cycle II, a significant improvement was observed, with 92% of students achieving the KKM. Based on these results, it can be concluded that the use of the Simulation method effectively enhances student learning outcomes in the topic of Infak. The researcher plans to continue the study into cycle III to achieve more optimal results.